Properties of Magnesia Composites According to Replacement Ratio of Perlite - Jeon-Ho Lee; Woo-Jun Hwang; Chang-Woo Lee; Sang-Soo Lee (Tehnički Glasnik, 2023)
Recently, passive and zero-energy construction has increased in Korea due to the government`s continuous application of budget-conscious policies for establishments. Accordingly, construction materials are being advanced, and the required performance standards for insulation materials are increasing. However, problems such as fire vulnerability and degradation of physical properties for organic and inorganic insulation materials are shown, so it is necessary to solve this problem. The objective of this research is to examine the properties of the composites by analyzing the flexural breaking load, impact resistance, density, VOCs concentration reduction rate, and fine dust concentration reduction rate of the composites manufactured based on the perlite substitution rate of the magnesia composites. The flexural breaking load test of the composites was assessed according to ‘KS F 3504’, a gypsum board standard and the impact resistance was assessed according to ‘KS F 4715’. The performance evaluation of adsorption performance of air pollutants of the VOCs and fine dust in the context of the small chamber technique suggested by Hanbat University. The results of this study are as follows: The flexural breaking load according to the perlite replacement rate tended to decrease as the perlite replacement rate increased. It is determined that the flexural breaking load is reduced by generating a large amount of pores inside due to the perlite porous structure characteristics. In the case of impact resistance, the impact resistance tended to increase as the perlite displacement rate increased. It is determined that the volume of the binder in the board is reduced, and pores inside the board are generated due to perlite, which is a porous material, thereby reducing the overall bonding force of the board. In the case of VOCs and fine dust concentrations, the VOCs and fine dust concentration reduction rates tended to increase as the perlite replacement rate increased. In the case of the perlite displace rate of 30%, the VOCs concentration decreased by 82.6%, and the fine dust concentration decreased by 87.9%. It has been established that the porous properties of perlite used to create a huge number of pores in the hardened body cause the concentration to be lowered physically through adsorption. This study's findings are thought to be fundamental information for securing the engineering properties and air pollution absorption of magnesia composites blended with perlite.